Analisis Karakter Kerja Sama pada Kegiatan Piket Kelas IV SD Kanisius Berdasarkan Konsep Thomas Lickona - Oktavia, Adella Dewi; Wardani, Irsya Naufa Ramadhina; Nurmala, Amalia; Fitrianti, Novia; Kiptiyah, Siti Maryatul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Cooperation is something that needs to be instilled in students even though there are still many who have not yet realized the character of cooperation in their daily lives. This research focuses on the character of cooperation in picket activities for fourth-grade students at Kanisius Elementary School. The aim of the research is to determine the application of students' cooperative character based on the concept of character education according to Thomas Lickona. The approach used in the research is a qualitative approach to understand how students interact and work together in picket activities. Data was collected through observation, interviews and documentation. The results of the research conducted show that the character of cooperation is inherent in Kanisius Elementary School students which can be seen in class picket activities. The average percentage of cooperation indicators is 89.5% in the very good category. This indicates that the cooperative character of the fourth-grade students at Kanisius Elementary School has been strongly instilled and is at the moral action stage based on the character development stage according to Thomas Lickona.